(untitled) (Bangladesh Pharmaceutical Journal, 2023)
Canna indica L., a perennial plant known as Indian shot and African arrowroot, is a member of the family Cannaceae. Historically, this plant was used to treat menstrual cramps, diarrhea and dysentery. The purpose of this investigation was to assess the antioxidant, cytotoxic, thrombolytic and membrane stabilizing activities of the methanol extract of C. indica leaf and its organic soluble fractions. The DPPH free radical scavenging method and the total phenolic content determination were utilized to evaluate the antioxidant capacity, whereas the brine shrimp lethality bioassay was implemented to study the cytotoxic potential. The ability of the extractives to prevent the hemolysis of red blood cells (RBC) in response to the application of heat and hypotonic solutions was used to estimate of their membrane stabilizing potential. In all of these experiments, the methanolic leaf extract (ME) displayed moderate activity, while the petroleum ether soluble fraction (PSF) and the dichloromethane soluble fraction (DSF) demonstrated the most promising antioxidant and cytotoxic activities among the extractives. However, the strongest thrombolytic and membrane stabilizing activities were observed by the chloroform soluble fraction (CSF). Additional research may be necessary to determine which phytoconstituents are most likely to be responsible for the aforementioned qualities. Bangladesh Pharmaceutical Journal 26(2): 162-166, 2023 (July)